The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1080/09640568.2010.508687
|View full text |Cite
|
Sign up to set email alerts
|

Extractive and Sustainable Development Reserves in Brazil: resilient alternatives to fisheries?

Abstract: This study uses the socio-ecological resilience concept to compare two categories of fisheries co-management in Brazil: Extractive and Sustainable Development Reserves. Ecological resilience was estimated by the indicators: reserve areas, human density and the existence of buffer zones around the reserves. Indicators for social-resilience were grouped in two categories: flexibility (assessed by livelihood diversification and resources exploited) and capacity to organize (assessed by local/governrnenta1 demand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 50 publications
0
29
0
2
Order By: Relevance
“…For example, a MPA recently enforced in the Paraty Bay has excluded fishers from fishing grounds and has not shown clear ecological nor socioeconomic benefits [44,45], while a recent law banned the catch of some endangered fish and invertebrate species, generating strong political opposition by fishers [24]. Besides being a cost-effective way to track temporal changes in resource abundance in the absence of regular monitoring [22,35], data from fishers' knowledge can provide a common ground for dialogue between fishers, biologists and managers [6], which can ultimately lead to comanagement initiatives [43]. These initiatives may include granting exclusive territorial rights to small-scale fishers [5,23], payments for ecosystem services or other compensation schemes to establish closed fishing seasons or protected areas [12], or diversification of economic activities by allocating more time to tourism [46].…”
Section: Policy and Management Implicationsmentioning
confidence: 97%
“…For example, a MPA recently enforced in the Paraty Bay has excluded fishers from fishing grounds and has not shown clear ecological nor socioeconomic benefits [44,45], while a recent law banned the catch of some endangered fish and invertebrate species, generating strong political opposition by fishers [24]. Besides being a cost-effective way to track temporal changes in resource abundance in the absence of regular monitoring [22,35], data from fishers' knowledge can provide a common ground for dialogue between fishers, biologists and managers [6], which can ultimately lead to comanagement initiatives [43]. These initiatives may include granting exclusive territorial rights to small-scale fishers [5,23], payments for ecosystem services or other compensation schemes to establish closed fishing seasons or protected areas [12], or diversification of economic activities by allocating more time to tourism [46].…”
Section: Policy and Management Implicationsmentioning
confidence: 97%
“…There is a growing body of research that addresses the question of resilience to climate change from different angles: by looking at climate change adaptation and resilience in specific fisheries SES (Cinner et al 2009a; Lopes et al 2011; Pinsky and Mantua 2014; Maldonado and Moreno-Sánchez 2014) by assessing the adaptive capacity of fisheries SES to confront climate change (Leith et al 2014; López-Angarita et al 2014; Rivera et al 2014); and by identifying attributes that safeguard economic (van Putten et al 2013) and ecological resilience for a given fishery (McClanahan et al 2012). However, no studies have suggested broadly applicable criteria for assessing socio-ecological resilience of fisheries.…”
Section: Introductionmentioning
confidence: 99%
“…The Brazilian Extractive Reserve is a type of protected area that allows people to live and keep their traditional livelihoods within the area, as long as it is considered sustainable. Such reserves are designed to be managed collaboratively by both government and local people (Fearnside 1989, Lopes et al 2011. Although the success of extractive reserves is ambiguous (Goeschl and Igliori 2004), MER has become the most frequent type of protected area addressing coastal artisanal fisheries in Brazil.…”
Section: Methodsmentioning
confidence: 99%